Engineering circular RNA for potent and stable translation in eukaryotic cells - R. Alexander Wesselhoeft (Nature Portfolio, 2018)
Circular RNAs have recently been shown to have protein-coding potential. Here the authors design a self-splicing RNA that, when circularized, provides for stable high-yield protein production.